2022
DOI: 10.3389/fmicb.2022.821968
|View full text |Cite
|
Sign up to set email alerts
|

High Mg/Ca Molar Ratios Promote Protodolomite Precipitation Induced by the Extreme Halophilic Bacterium Vibrio harveyi QPL2

Abstract: Bacterial activities have been demonstrated as critical for protodolomite precipitation in specific aqueous conditions, whereas the relationship between the various hydrochemical factors and bacterial activity has not been fully explored. In this study, biomineralization experiments were conducted using a newly isolated extreme halophilic bacterium from salina mud, Vibrio harveyi QPL2, under various Mg/Ca molar ratios (0, 3, 6, 10, and 12) and a salinity of 200‰. The mineral phases, elemental composition, morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 80 publications
3
11
0
Order By: Relevance
“…Thus, the halophilic V. harveyi seems to have played a role in the production of calcite and vaterite in our reaction media. V. harveyi is a well-known hyperhalophilic bacteria (Wang et al, 2022;Han et al, 2022) whose ability to precipitate calcite was reported under extreme halophilic conditions. According to our results, this bacterium seems to be able inducing MICP also in non-halophilic media.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the halophilic V. harveyi seems to have played a role in the production of calcite and vaterite in our reaction media. V. harveyi is a well-known hyperhalophilic bacteria (Wang et al, 2022;Han et al, 2022) whose ability to precipitate calcite was reported under extreme halophilic conditions. According to our results, this bacterium seems to be able inducing MICP also in non-halophilic media.…”
Section: Resultsmentioning
confidence: 99%
“… 25 , 31 The P 2p peak can be ascribed to P–O at 132.8–133.2 eV. 32 The peak of S 2p can be ascribed to S–S at 168.4 and 164.4 eV. Through the XPS analysis, several elements on the surface of minerals constitute different organic functional groups; this is useful to further prove the important influence of organic molecules in the process of mineralization.…”
Section: Resultsmentioning
confidence: 99%
“…The first peak 531.0 eV of O 1s may be attributed to CO 3 , another peak associated with C–O (532.2–532.8 eV). N 1s appeared at a binding energy of 399.5 and 399.7 eV (C–NH 2 ) and is attributable to nonprotonated nitrogen from amines and amides. , The P 2p peak can be ascribed to P–O at 132.8–133.2 eV . The peak of S 2p can be ascribed to S–S at 168.4 and 164.4 eV.…”
Section: Resultsmentioning
confidence: 99%
“…The “dolomite enigma” has been a mystery for two centuries at least; compared to the common occurrence in pre-Holocene strata, dolomite is relatively rare in modern marine sediments ( de Dolomieu, 1791 ; Gregg et al, 2015 ; Qiu et al, 2017 ; Zheng et al, 2021 ). After various experiments over many decades, a most popular way to synthesize dolomite in laboratory experiments under earth surface conditions has been to utilize microbes ( Sánchez-Román et al, 2009 , 2011 ; Qiu et al, 2019 ; Liu et al, 2020 ; Han et al, 2022 ). The replacement of Ca 2+ ions by Mg 2+ ions in carbonate minerals has been regarded as the major reason for the formation of dolomite, but this has rarely been reported from laboratory experiments at Earth surface conditions ( Kaczmarek and Thornton, 2017 ; Zheng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%